Transformasi sistem informasi akuntansi menuju enterprise resource planning pada PT. Cipta Daya Inovasi - Muhammad Yusuf Tamim; Isti Rahayu (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2026)
This study aims to examine the transformation process of the accounting information system at PT. Cipta Daya Inovasi, from a manual system to an integrated system based on Enterprise Resource Planning (ERP) Odoo. The research method used is descriptive with a qualitative approach, employing techniques such as interviews, observations, and documentation. The findings indicate that the transformation was carried out to improve efficiency, accuracy, and financial data integration in order to support reporting and consolidation processes with the holding company. The implementation process began with the application of the Sales and Expenses modules. The company’s human resources demonstrated a high level of readiness after comprehensive training, enabling them to adapt to and operate the system effectively. Overall, the implementation of ERP Odoo has proven to enhance the effectiveness of financial reporting, facilitate the consolidation process, and support the company’s digital transformation initiatives.